Generation of soil maps permeability. Case study in two cantons of Loja province, Ecuador - Espinosa Marín, Jorge Andrés (2023)
The generation of permeability maps is based on the analysis and interpretation of geology, environmental morphology, land use, and slope, which enables the selection of sampling areas with similar characteristics. The method represents the integration of the physical characteristics of the study area and then determines the infiltration capacity differences in the most representative geopedologic units. In determining the basic data, minidisc infiltrometers were used to perform seventy-two infiltration tests in different types of soils with varying organic matter content, texture, soil structure, and vegetation cover, which showed the spatial variability that exists in two cantons of Loja province, Ecuador. In addition, it was observed that the infiltration rate depended mainly on the content of the organic matter in the soil and is consistent with information collected on permeability worldwide. In this study, generated pedotransfer function (FTP) coefficient of determination R2 0.78, the determination of the coefficient indicates a satisfactory estimate of the permeability with the variables that were analyzed; in addition, the methodology for assessing the permeability was suitable for the conditions of this investigation. For this reason, the method described here should be tested in other areas of the country with a greater number of field trials and with more variable contents of organic matter and soil textural classes.